2016
DOI: 10.5535/arm.2016.40.3.440
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Dysphagia Scale Is a Useful Tool for Predicting Aspiration Pneumonia in Patients With Parkinson Disease

Abstract: ObjectiveTo describe the correlation between the functional dysphagia scale and aspiration pneumonia and which characteristics influence the occurrence of aspiration pneumonia in patients with idiopathic Parkinson disease.MethodsFifty-three patients with idiopathic Parkinson disease were prospectively evaluated in this study. Disease severity and functional status were measured by modified Hoehn and Yahr (H&Y) staging, Schwab and England activities of daily living (S-E ADL) scale and Korean version of Mini-Men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 28 publications
1
22
0
2
Order By: Relevance
“…Lee JH, et al [ 13 ] and Argolo N, et al [ 14 ] examined VFSS parameters in patients with PD. In their studies, pharyngeal residue, pharyngeal transit time, or piecemeal deglutition are specific predictors of aspiration in PD, and also in our study, all the parameters of pharyngeal phase, including these three parameters, were significantly associated with the development of aspiration pneumonia ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lee JH, et al [ 13 ] and Argolo N, et al [ 14 ] examined VFSS parameters in patients with PD. In their studies, pharyngeal residue, pharyngeal transit time, or piecemeal deglutition are specific predictors of aspiration in PD, and also in our study, all the parameters of pharyngeal phase, including these three parameters, were significantly associated with the development of aspiration pneumonia ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…One study showed a link between treated dental caries and a decreased risk of pneumonia among PD patients, which suggests that aspiration pneumonia plays an important role in this group of patients [ 12 ]. The other study demonstrated that the functional dysphagia scale could be used to predict aspiration pneumonia in PD patients [ 13 ]. Furthermore, ventilatory dysfunction including lung volume, respiratory muscle weakness, and sleep breathing disorders were all affected in PD patients [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was no scale for the “recommended” criteria that is proven to be valid, reliable, and sensitive in clinical studies. A recent study showed that the functional dysphagia scale (FDS) and the Schwab and England activities of daily living (S-E ADL) scale can effectively predict the occurrence of aspiration pneumonia in patients with PD [42]. Clinical scales of nonmotor symptoms relating to dysphagia for patients with PD are summarized in Table 2 [39].…”
Section: Parkinson’s Diseasementioning
confidence: 99%